What is the Hidden Biological Mechanism Underlying the Possible SARS-CoV-2 Vertical Transmission? A Mini Review - Sessa, Rosa; Anastasi, Emanuela; Brandolino, Gabriella; Brunelli, Roberto; Di Pietro, Marisa; Filardo, Simone; Masciullo, Luisa; Terrin, Gianluca; Viscardi, Maria Federica; Porpora, Maria Grazia (Frontiers in Physiology, 2022)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS- CoV-2) represents an emerging infection that is spreading around the world. Among susceptible patients, pregnant women are more likely to develop serious complications and negative obstetric outcomes. Vertical transmission constitutes a debating issue which has been not completely understood. This review aims at describing the currently available evidence on SARS-CoV2 vertical transmission. We carried out a computerized literature search in the Cochrane Library, PubMed, Scopus and Web of Science, selecting the most relevant studies on vertical transmission from the outbreak onset until February 2022. The analysis of the available literature identifies the presence of SARS-CoV2 genome in different biological specimens, confirming the hypothesis that a transplacental infection can occur. In spite of the high number of infected people around the world, mother-to-child infections have been infrequently reported but it can be observed under certain biologic conditions. A deep knowledge of the underlying mechanisms of SARS-CoV2 vertical transmission is of paramount importance for planning an adequate management for the affected mothers and newborns.